“Pygmalion Effect”: Modern Artists In The Age Of Instagram - Rachmayuningtyas, Veronika Alma (Institut Seni Indonesia Yogyakarta, 2022)
Instagram is an image-based social media that provides online photo or video sharing services. In the art world, Instagram occupies the top position for modern artists to publish their work. However, there is very little information about the features of the art that are most in demand, and what role is present in the interaction between artists and followers in the works of art that are most favored. Starting from a Greek myth, the Pygmalion effect was finally developed in the real world by Robert Rosenthal who later gave birth to the theory: Self-fulfilling Prophecy. This study extends research on social media interactions in the art world which is important for research on the interactive psychology of artwork and digital marketing communications in social media.This article uses qualitative and artistic research methods to analyze the interaction between artists and followers on Instagram and the most preferred features of the artwork using the Pygmalion effect as a theoretical basis. Is there feedback between the artist and his followers? How big is the impact of the Pygmalion effect on the artist's interest in work or productivity?